Pengaruh Model Pembelajaran Tutor Sebaya Berbantuan Media Video Pembelajaran Terhadap Kompetensi Pengetahuan IPA kelas V SD Gugus III Kecamatan Tabanan - Ni Made Dini Rahayu; I Komang Ngurah Wiyasa (Journal for Lesson and Learning Studies, 2023)
The current low mastery of science competencies is because it is still considered difficult for some students. The lack of optimal mastery of competencies, especially science, is due to the fact that the teaching carried out by the teacher does not provide sufficient understanding to students. The purpose of this research is to describe the science knowledge competence of fifth grade students after being taught a peer tutor learning model assisted by instructional video media to fifth grade students at SD Gugus III, Tabanan District, in the 2022/2023 academic year. The type of research used is a quasi-experimental design with nonequivalent control group design. The population in this study were all fifth grade students at Gugus III Public Elementary School, Tabanan District, 2022/2023 academic year, consisting of 152 people. The entire population is equated with the Anava test. After the population was declared equal, the sampling in this study was carried out using the cluster random sampling technique. Based on the results of the t-test calculation These results show that tcount is greater than ttable, so H0 is rejected and Ha is accepted. There is a significant difference in the competence of science knowledge between the group of students who were taught the peer tutor learning model assisted by learning videos and the group of students who were taught conventional learning in class V SD Gugus III, Tabanan District, Academic Year 2022/2023. Thus it can be concluded that the peer tutor learning model assisted by learning video media has an effect on the competence of science knowledge in class V SD Negeri Gugus III Tabanan District in the 2022/2023 academic year.